Baricitinib with cyclosporine eliminates acute graft rejection in fully mismatched skin and heart transplant models - Abboud, Ramzi; Kim, Sena; Staser, Karl; Jayasinghe, Reyka G.; Lim, Sora; Amatya, Parmeshwar; Frye, C. Corbin; Kopecky, Benjamin; Ritchey, Julie; Gao, Feng; Lavine, Kory; Kreisel, Daniel; et al. (Frontiers in Immunology, 2023)
Solid organ transplant represents a potentially lifesaving procedure for patients suffering from end-stage heart, lung, liver, and kidney failure. However, rejection remains a significant source of morbidity and immunosuppressive medications have significant toxicities. Janus kinase (JAK) inhibitors are effective immunosuppressants in autoimmune diseases and graft versus host disease after allogeneic hematopoietic cell transplantation. Here we examine the role of JAK inhibition in preclinical fully major histocompatibility mismatched skin and heart allograft models. Baricitinib combined with cyclosporine A (CsA) preserved fully major histocompatibility mismatched skin grafts for the entirety of a 111-day experimental period. In baricitinib plus CsA treated mice, circulating CD4+T-bet+ T cells, CD8+T-bet+ T cells, and CD4+FOXP3+ regulatory T cells were reduced. Single cell RNA sequencing revealed a unique expression profile in immune cells in the skin of baricitinib plus CsA treated mice, including decreased inflammatory neutrophils and increased CCR2- macrophages. In a fully major histocompatibility mismatched mismatched heart allograft model, baricitinib plus CsA prevented graft rejection for the entire 28-day treatment period compared with 9 days in controls. Our findings establish that the combination of baricitinib and CsA prevents rejection in allogeneic skin and heart graft models and supports the study of JAK inhibitors in human solid organ transplantation.